Work Posture Analysis of Welding Workers Using the RULA Method - Surahma; Berliana Suroso; Febriyani Prastike (Newinera Publisher, 2020)
Work posture is a point that can determine an analysis of how effective the work is done. This study aims to analyze the working posture of Las Manggaraya workshop workers using the Rapid Upper Limb Assessment (RULA) method. This research collects anthropometric data which is part of ergonomics that specifically studies about ways to find out body size. In using the Rapid Upper Limb Assessment (RULA) method, every movement made will be given a predetermined score. The results showed that 5 out of 8 workflow processes have RULA scores with severe and very western risk level, which means that it is necessary to change work postures as soon as possible or as soon as possible. Overall the RULA score is at a level of severe and very severe risk so that changes in work posture are required